Epidemiological characteristics of imported malaria related to international travel in the Republic of Korea from 2009 to 2018 - Byoung Hak Jeon; Jung Ah Lee; Shin Young Lee; Sang Eun Lee; Joon Sup Yeom (Scientific Reports)
Abstract Malaria, transmitted by mosquitoes infected with Plasmodium parasites, remains a significant health issue with global travel increasing the risk of imported malaria. This study investigates imported malaria cases in the Republic of Korea from 2009 to 2018 using data from the Korea National Infectious Disease Surveillance System. During this period, 601 imported cases were reported, with 82.4% male patients and a median age of 39.1 years. Most cases (76.5%) involved Korean residents returning from malaria-endemic areas, mainly Africa and Asia. Plasmodium falciparum (55.7%) and Plasmodium vivax (30.3%) were the predominant species. The annual percent change in incidence rate was 6.45%. Notably, 71.5% of the patients did not receive prophylactic chemotherapy, and 18% of those who did still developed malaria. Median diagnostic delays were 4 days for P. falciparum and 7 days for P. vivax. The case fatality rate was 2.3%, with all deaths occurring in travelers who contracted P. falciparum in Africa. This study emphasizes the ongoing risk of imported malaria in the ROK and highlights the need for better awareness and preventive measures among travelers. Enhancing surveillance and educating travelers on anti-malaria chemoprophylaxis are crucial.